Pengaruh Kepemimpinan Transaksional, Beban Kerja dan Lingkungan Kerja terhadap Kinerja Aparatur Sipil Negara Melalui Work Engagement dan Kepuasan Kerja - Walfaidhin; Muhtar Sapiri; Zainur Hidayah (Al-Buhuts, 2024)
The purpose of this study is to examine and analyze the influence of transactional leadership, workload, and work environment on the performance of civil servants (ASN) through work engagement and job satisfaction at the Representative Office of BKKBN in West Sulawesi Province. This research employs a quantitative design with a sample size of 53 employees. Data collection was conducted using questionnaires, and the data were analyzed using SmartPLS version 4.1.0.8. The findings reveal that transactional leadership has a positive influence on the performance of civil servants. The workload assigned to civil servants also positively affects their performance. However, there is no evidence that the work environment directly influences the performance of civil servants. Work engagement significantly affects civil servants’ performance, and job satisfaction has a notable impact on improving their performance. Transactional leadership not only directly influences the performance of civil servants but also indirectly through job satisfaction. Workload influences performance through work engagement, while job satisfaction partially mediates the effect of transactional leadership on civil servant performance. Similarly, job satisfaction mediates the influence of workload on performance. However, the work environment does not directly contribute to improving civil servants' performance